Change in home language environment and English literacy achievement over time: A multi-group latent growth curve modeling investigation. (October 2020) - Kim, Hyunah; Barron, Christine; Sinclair, Jeanne; Eunhee Jang, Eunice
In most studies investigating the educational outcomes of linguistically diverse students, variables that identify this population have been considered as static. In reality, owing to the dynamic nature of students and their families, students' home language environments change over time. This study aims to understand how elementary school students' home language environments change over time, and how longitudinal patterns of English literacy achievement across grades 3, 6, and 10 differ among students with various home language shift patterns in Ontario, Canada. The longitudinal cohort data of 89, 609 students between grades 3 and 10 from the provincial assessments were analyzed for changes in their home language environment. A subsample of 18, 000 students was used to examine different patterns of relative literacy performance over time and their associations with immigration background and early intervention programming using multi-group latent growth curve modeling. Our findings suggest a strong movement toward an English-dominant home language environment among multilingual students; yet, students whose homes remained as multilingual demonstrated the highest literacy achievement in the early grade as well as the highest improvement in relative performance over time. The paper draws implications for promoting students' home language, instilling a positive view of multilingual competence.